Quality of Vending Machine Water in Bangkok - Janwithayanuchit, Isaya; Chuwongwattana, Sumonrat; Phumeesat, Potjaman; Rangsipanuratn, Watcharin; Paungmoung, Porntip (Journal of Health Science of Thailand, 2017)
As water vending machines became popular in Bangkok, studies describing the qualities of water from the machines are still scarce. A total of 546 water samples, comprising 20 different brands of vending machines, were randomly collected from 30 districts in Bangkok during March - June 2005 and their physical and microbiological qualities were assessed. As a result, the levels of pH, temperature, color, odor and taste of 39 samples (7.1%) exceeded drinking water standards. In microbiological examinations, exceedances of the standards were found in cases of heterotrophic bacteria (>500 colony/ml) in 203 samples (37.2%), total coliforms (MPN >2.2) in 49 samples (9%), Escherichia coli in 36 samples (6.6%), Pseudomonas aeruginosa in 118 samples (21.6%) and algae in 7 samples (1.3%). Salmonellae and Staphylococcus aureus were not isolated from any sample. The results indicated that the qualities of the 52.9 percent of samples collected from water vending machines were critical therefore consumers should be very careful and duly well informed about water quality of vending machines.